Pious Landlords: Confraternal Landownership in 1561 Florence - Majda, Natalie (Confraternitas)

(untitled) (Iter Press, 2022)
This article maps and analyses patterns of confraternal land ownership (commercial and residential) using public data made available through DECIMA’s WebGIS tool that maps the 1561 Decima ricerca among other historic documents. Analysis of confraternal property data identifies social, economic, and spatial organisation patterns and use of property to support charitable work, supplement group funding, house staff and members, and more. GIS mapping of DECIMA data allows for 1561 Florentine confraternal property ownership to be mapped city-wide, creating opportunities for new and exciting academic examinations and testing of theories such as laudesi versus disciplinati geographic spread. All article maps have public links below the map descriptions which may be used to explore, manipulate, and draw from embedded 1561 Decima ricerca data as desired.